(untitled) (Panacea Journal of Medical Sciences, 2024)
Introduction: Neonatal infection could be a major reason for death and illness in new borns, significantly in growing countries. To minimize neonatal sepsis-related morbidity and mortality, paediatricians must thoroughly understand the bacterial flora present and their pattern of susceptibility to antibiotics. This study focused to investigate the etiological profile of culture-positive sepsis and antibiotics sensitivity pattern. Material and Methods: All neonates hospitalized in the critical care unit of the government general hospital in Srikakulam were included in this prospective study, which was done over the course of a year from January 2021 to December 2021. All infants with a positive blood culture and a medical diagnosis of sepsis were identified. All neonate demographics, clinical information, parental risk factors, bacterial profiles, and patterns of antibiotic sensitivity were noted and analysed. Results: A total of 556 newborns admission to the NICU during the study period out of these 282 cases were diagnosed as neonatal sepsis out of these 282 neonatal sepsis cases 52 cases were culture-positive sepsis. Most bacterial isolates from culture-positive sepsis were gram-negative, predominantly ad and they are having good susceptibility to meropenem, cefotaxime and amikacin. cultures with gram-positive species staphylococci were the most common microorganisms and it was good susceptibility to piperacillin-tazobactam and linezolid. Conclusion: in the present study , and were the more frequently isolated microorganisms, these organisms are very well susceptible to meropenem, cefotaxime and amikacin. So we recommend cefotaxime and amikacin as the first line of treatment in our institution and meropenem and piperacillin-tazobactam as the second line of empirical therapy in our institution.